The Effect of a Psychological Counseling Program to reduce irrational ideas and the causal attribution of the coaches of the gymnasium sports care center - Abd-Ulwahid , Baydaa (Journal of Physical Education, 2024)
The research aimed to prepare a psychological counseling program for the coaches of the Sports Care Center in the gymnasium, and to learn about the impact of the psychological counseling program in reducing irrational ideas and causal attribution of the coaches of the Sports Talent Care Center in the gymnasium, to assume that there are statistically significant differences between the results of the tribal and posttests of the research group Experimental in the scale of irrational ideas, and there are statistically significant differences between the results of the tribal and posttests of the experimental research group in the scale of the causal attribution scale, The experimental approach was adopted by designing one experimental group, and the current research problem population was represented by coaches of various categories at the National Center for Nurturing Sports Talent in Gymnastics in Baghdad, a total of (18) coaches for the adult (2023/2024) sports season. The main research sample for application was chosen from them intentionally using a survey method. The number of the procedural research group, whose arithmetic mean exceeded the hypothesized mean for the scales of irrational thoughts and causal attribution, reached (12) trainers to represent the experimental research group with a percentage of (66.667%) of their community of origin. The research procedures for building the two measurement tools of the paper-and-pencil type also required selecting a similar sample from outside the boundaries of the problem. The research procedures concerned them with verification of scientific conditions and statistical analysis, and (43) coaches from clubs in the capital, Baghdad, were chosen for them. And after the completion of the construction of the two scales, (7) counseling sessions were prepared and applied in the research experience on the experimental group coaches, and then tackled their results with a system (SPSS), and the conclusions were that the irrational ideas and the causal attribution of the coaches of the gym gynecology center enjoyed the conditions and scientific transactions to accept tools Sikomitry measurement in sports psychology, and the preparation of the psychological counseling program based on reducing the level of irrational ideas and causal attribution is suitable for the coaches of the Sports Talent Care Center in the gymnasium, and the psychological counseling program helps in reducing the level of irrational ideas and the causal attribution of the coaches of the Sports Care Center in the gymnasium, As for the research recommendations, it is necessary that it is necessary to pay attention to the gymnasium measurement according to the determinants of mathematical psychology to track the condition of the coaches of the Sports.